How Stale Central Bank Interest Rate Projections Affect Interest Rate Uncertainty - Gunda-Alexandra Detmers; Dieter Nautz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The Reserve Bank of New Zealand guides interest rate expectations of financial markets by projections of future short-term rates that are updated only once a quarter. As a consequence, projections become stale when time evolves and new information enters the market. This paper investigates the dynamic impact of probably outdated interest rate projections on the expectations management of central banks. Confirming the stabilizing effect of fresh central bank announcements, we show that interest rate uncertainty increases with the time elapsing since the recent interest rate projection. In contrast, we find that stale projections may hamper central bank communication. In fact, interest rate uncertainty increases when the market perceives the projections to be outdated.
Keywords: E52; E58; G14; 330